Teachers’ Work and Working Conditions: Collaborating To Drive Change - McGrath-Champ, Susan; Stacey, Meghan; Fitzgerald, Scott; Gavin, Mihajla; Wilson, Rachel (New South Wales Teachers' Federation, 2023)
Susan McGrath-Champ et al. introduce a series of articles on teachers’ work and working conditions. Their work provides an update to “Understanding work in schools, The Foundation for teaching and learning”, the 2018 report to the NSW Teachers Federation. The report examined the administrative demands that encroach on the work of teachers and impede their capacity to focus on tasks directly related to their teaching and to students’ learning.